Quinquangulin and Rubrofusarin: A Spectroscopy Study - Moreira, Leonardo Marmo; Lyon, Juliana Pereira; Lima, Adriana; Codognoto, Lúcia; Machado, Antonio E. H.; Tiago, Fernanda de S.; Araújo, Diesley M. S.; Silva, Expedito Leite; Hioka, Noboru; Rodrigues, Máira Regina; Bonacin, Juliano Alves; dos Santos, Sandra Cruz; et al. (Orbital: The Electronic Journal of Chemistry, 2017)
In this work, excitation and emission spectra were evaluated in order to elucidate the properties of quinguangulin and rubrofusarin in water/ethanol mixture. The study demonstrates that the maximum excitation wavelength can be significantly modulated changing the proportion of organic solvent in the water/organic solvent system. Quinquangulin presented the higher wavelength of maximum excitation in an ethanol-water mixture containing 70% of water. Probably, the organization between ethanol and water molecules in this condition favors the formation of strong polar interactions with the π* orbitals of naphthopyrones. It is interesting to register that the additional methyl group in quinquangulin seems to develop a decisive function related to the ability to formation of hydrogen bonds, altering significantly the mechanism of solute-solvent interaction. This work, which involves theoretical and experimental analyses, demonstrates the relevance of the studies focused on solvent mixtures as well as emphasizes the potential of quinguangulin and rubrofusarin as photosensitizers. DOI: http://dx.doi.org/10.17807/orbital.v9i4.1043